Study for the preparation of Cu2+-doped twin spherical MnCO3 structure as an anode material for high-performance lithium-ion batteries. Issue 37 (15th September 2021) - Dong, Fangyuan; Dong, Xuelu; Xu, Shuling; Li, Haibo; Zeng, Suyuan; Fu, Chonggang; Wang, Lei
Abstract : Cu 2+ -Doped twin spherical MnCO3 microstructure was prepared, characterized and used as an anode for the lithium-ion battery. After 600 cycles, a reversible capacity of 810 mA h g −1 was retained. Excellent rate property and cyclability were attained. Abstract : Monodispersed Cu 2+ -doped twin spherical MnCO3 microstructures with a ratio of length to brachyaxis about 1.5 : 1 were prepared, characterized and used as an anode for the preparation of lithium-ion batteries. After 600 cycles, a reversible capacity of 810 mA h g −1 was retained. Excellent rate performance and cyclability were attained.